MEN'S ACCESSIBILITY TO THE PRIMARY CARE SERVICES:AN APROXIMATION WITH THE BIOETHICS OF PROTECTION - Doane Martins da Silva; Tatiane Oliveira de Souza; Maristela Viana Lima; Sérgio Donha Yarid; Edite Lago da Silva Sena (Universidade Federal do Paraná, 2013)
This bibliographic study aimed to analyze studies on the issue of men's accessibility to the Primary Care Services following the implementation of the National Comprehensive Healthcare Policy for Men, engaging this topic with the bioethics of protection. 10 studies were analyzed, from the period 2009 - 2012, published in the databases indexed in the Virtual Health Library. The discussion of the information was structured in two themes: Difficulties in accessing the Primary Care Services revealed by the men and The man's accessibility to the Primary Care Services: an ethical problem. The material reviewed evidences the existence of factors related to the functioning of the services and to the stereotype of masculinity constructed culturally, both of which hinder men's access to the services. It is considered beneficial to address bio-ethics in the context of this accessibility, as the issue represents, effectively, an ethical problem in the field of public health.